Molecular detection of EGFRvIII-positive cells in the peripheral blood of breast cancer patients - Silva, HA (2006)
The aim of this study is to evaluate epidermal growth factor receptor variant III, EGFRvIII, a cancer specific mutant, as a possible marker for the diagnosis of breast cancer occult systemic disease. EGFRvIII mRNA was identified by an RT-nested PCR with a high sensitivity. In 102 women studied, the mutant was detected in the peripheral blood of 30% of 33 low risk, early stage patients, in 56% of 18 patients selected for neoadjuvant chemotherapy, in 63.6% of 11 patients with disseminated disease and 0% of 40 control women. In low risk, early stage patients, the presence of one or more tumour characteristics predicting recurrence such as the absence of oestrogen receptors and the presence of ERBB2 or histologic grades G2/G3 was significantly associated with EFGRvIII detection (p<0.05). EGFRvIII mRNA has characteristics to be a useful marker for the diagnosis of occult systemic disease in breast cancer. Follow-up studies will evaluate its clinical value as a decision criterion for systemic therapy.